The role of diplomacy in the delivery of regional public goods with specific reference to the Department of International Relations and Cooperation (DIRCO) in southern Africa - Du Plessis, Anton (University of Pretoria, 2013)
Dissertation (MDiplomatic Studies)--University of Pretoria, 2013.